PROTEINURIA DALAM STROK DISERTAI DIABETES MELITUS DAN TANPA DISERTAI DIABETES MELITUS - Misnah Misnah; Suci Aprianti; Fitriani Mangerangi; Burhanuddin Bahar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Proteinuria is a predictor of stroke in diabetic and non diabetic patients, but remains poorly documented from the available researchstudies. The aim of this study is to determine. Proteinuria in stroke (Hemorrhagic and non Hemorrhagic) patients which suffer diabeticand non diabetic. A cross sectional study had been done in stroke patients, diabetics and non diabetics who were hospitalized at theWahidin Sudirohusodo Hospital Makassar during the period of May to July 2010. Urine samples were analyzed using a dipstick method.There were 30 samples of non Hemorrhagic stroke (NHS) with diabetics: 71.4% with proteinuria; Hemorrhagic stroke (HS) with diabetics:87.5% with proteinuria (p = 0.55). Non diabetic HS: 100% with proteinuria; Non diabetic NHS: 40% with proteinuria; (p=0.04).Proteinuria in stroke could occur either in diabetic or non diabetic subjects, but proteinuria was higher in HS the existence of diabetes.Further research is needed on the role of proteinuria in stroke in terms of diagnostic or prognostic values.